(log x) = 1/x ⇒ ∫1/x dx = log |x| + C
(ex) = ex ⇒ ex dx = ex + C
(-cos x) = sin x ⇒ ∫ sin x dx = - cos x + C
(sin x) = cos x ⇒ ∫cos x dx = sinx + C
(tanx) = sec²x ⇒ ∫sec²x dx = tanx + C
(-cotx) = cosec²x ⇒ ∫cosec²x dx = - cot x + C
(sec x) = sec x tan x ⇒ ∫sec x tan x dx = sec x + C
(- cosec x) = cosec x cot x ⇒ ∫cosec x cot x dx = - cosec x + C
(log sin x) = cot x ⇒ cot x dx = log |sinx| + C
(-log cos x) = tan x ⇒ tan x dx = - log |cos x| + C
(log (sec x + tan x)) = sec x ⇒ ∫sec x dx = log |sec x + tan x| + C
-
(log (cosec x – cot x)) = cosec x ⇒ ∫cosec x dx = log |cosec x – cot x| + C
Sunday, May 7, 2017
Fundamental formulas on integration
Subscribe to:
Post Comments (Atom)
No comments:
Post a Comment